2019
DOI: 10.53383/100280
|View full text |Cite
|
Sign up to set email alerts
|

International Real Estate Review

Abstract: In recent years, China has uniquely implemented various policies to control housing prices, particularly its property- purchasing limitation policy. This research proposes a vector autoregression (VAR) model with likelihood-ratio (LR) tests to examine the effects of such a policy on housing prices at the national, provincial and city levels in China, with the use of monthly data from 2002 to 2013. The results show that at the national level, the effect of the policy is very significant, and the impact on housi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The implementation of real estate purchase restrictions as a pivotal measure f or government control in the real estate market primarily suppresses the surge in housing prices within restricted zones. Its inhibitory impact exhibits strong regional characteristics, manifesting variations at the urban level (An, Zou, Zhang, & Gupta, 2019;Du & Zhang, 2015;Gong, De Haan, & Boelhouwer, 2020;Jia, Wang, & Fan, 2018;Sun, Zheng, Geltner, & Wang, 2017;Yuan, Wu, Wei, & Wang, 2018). Chen, Hui, Seiler, and Zhang (2018) found that the purchase restriction policy can restrain the housing price in the current period, but the change in population stru cture will eventually lead to a housing price rise.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of real estate purchase restrictions as a pivotal measure f or government control in the real estate market primarily suppresses the surge in housing prices within restricted zones. Its inhibitory impact exhibits strong regional characteristics, manifesting variations at the urban level (An, Zou, Zhang, & Gupta, 2019;Du & Zhang, 2015;Gong, De Haan, & Boelhouwer, 2020;Jia, Wang, & Fan, 2018;Sun, Zheng, Geltner, & Wang, 2017;Yuan, Wu, Wei, & Wang, 2018). Chen, Hui, Seiler, and Zhang (2018) found that the purchase restriction policy can restrain the housing price in the current period, but the change in population stru cture will eventually lead to a housing price rise.…”
Section: Introductionmentioning
confidence: 99%